Pengaruh Terapi Kombinasi Brandt Daroff dan Aromaterapi Peppermint terhadap Skala Nyeri Kepala pada Pasien Vertigo - Ulya Rohmatul Faizun; Retno Setyawati; Erna Melastuti (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Vertigo is frequently accompanied by headache that disrupts comfort and daily function, thus requiring effective nonpharmacological interventions. This study aimed to determine the effect of a combined therapy of Brandt-Daroff exercises and peppermint aromatherapy on headache pain intensity among vertigo patients. A pre-experimental one-group pretest–posttest design was applied with 14 hospitalized patients as respondents. Headache intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. Prior to treatment, most participants experienced moderate pain (64.3%), while 28.6% reported severe pain and 7.1% reported very severe pain. After the intervention, pain distribution shifted markedly, with 85.7% experiencing mild pain and 14.3% reporting no pain. Wilcoxon signed-rank test revealed a significant difference between pretest and posttest scores (Z = -3.316; p = 0.001). These findings indicate that the combined Brandt-Daroff and peppermint aromatherapy intervention effectively reduces headache pain intensity in vertigo patients and may be recommended as a complementary nursing intervention to improve patient comfort and symptom control.